Migrating objects: John Henry Foley and empire - Cullen, Fintan (Cambridge Scholars Press, 2017)
This is a chapter in a book entitled, Artists and Migration 1400-1850. Britain, Europe and beyond, edited by Kathrin Wagner, Jessica David and Matej Klemencic, published by Cambridge Scholars Press in 2017. The collection came out of a conference in Liverpool in 2013. My chapter considers the equestrian statue of a Raj military figure James Outram which was erected in central Calcutta in 1874. The essay discusses the incongruity of using western artistic ideals in the context of 19th C India. The conclusion is about the paradox of an Irish-born sculptor contributing to the imperial game.